Bibliometric Analysis of Social Desirability - Yurtcu, Meltem; Koçoğlu, Erol (Journal of History Culture and Art Research, 2020)
Several studies conducted to measure and determine the perceptions of the individual and the society on various issues presented and compared numerical sociological and psychological finding data. The perceptions determined about the study subject are influenced by social desirability, one of the personality inventory elements. The study was based on the visualization of the descriptive structure. In the study, CiteSpace software was used to develop and visualize the network structure. Web of Science database was used in CiteSpace software. Web of ScienceTM core collection database was searched for the term "Social Desirability" with abstract, author keywords, and Keywords Plus forms. In total, 5,489 studies on the subject were accessed. These studies were conducted in a total of 171 different fields including psychology, management, health, and educational research. The findings demonstrated that the concept of social desirability was comprehensively studied in various fields, and a knowledge map was developed based on these various fields.